The semantic use of the image of the image of Algerian child in revolutionary cinematographic discourse: A semiological analysis of a sample of extracts from the film the Children of November " directed by Moussa Haddad - Maayache, Idir; Rachedi, Ouardia (Journal of Human Sciences, 2022)
This study tries to identify the image given to Algerian children through the cinematographic discourse of the Algerian revolution in order to understand the connotations of this image by identifying their links with historical and ideological reality. To achieve this goal, we interpreted each element of the cinematographic language used in a symbolic way in the film "the children of November" directed by Moussa Haddad, using the semiological approach of the cinematographic discourse which is essentially based on the technical cutting. and the denotative and connotative reading of each sign constituting this discourse. And since the semiological reading of historical reality requires the comparison of facts; we compared the meanings mentioned in the film and the actual depictions of the Algerian revolution with the help of documentation necessary to illustrate the facts.